Menejemen Pembentukan Karakter Religius Melalui Kegiatan Keagamaan di SMK Manbaul’ulum Cirebon - Ibrohim, Mohamad; Kambali, Kambali; Suklani, Suklani (UNIVERSITAS SERAMBI MEKKAH, 2025)
The background of the problem in this research is the lack of religious nature of students which is particularly important for students. This can determine whether they are accepted in the industrial work, especially in the community. Because this religious character is important and must be owned by all students of SMK Manbaul Ulum and the surrounding community.This research aims to find out and analyze the impact of religious activities on the religious character of SMK Manbaul Ulum students, so that hope the school, parents and the community can be improved to improve the quality of the students themselves.The approach used in this research is a qualitative approach, with a type of qualitative descriptive research and the design of this research is a case study. The data collection techniques themselves use Observation, Interviews, and Documentation.The results obtained from the research are the improvement of the religious character of students, such as the implementation of religious habituation activities at SMK Manbaul Ulum, by carrying out the habituation of congregational prayers, reading the Qur’an and religious lectures. To produce a significant increase in religious character. Against the santri or students at SMK Manbaul Ulum Dukupuntang Cirebon Regency. This research is expected to be useful for readers and can be used as a reference for researchers who are looking for the same material, so that it can be compared and strengthened by other researchers.